MINDERE WELVAART COMMISION DAN PERSOALAN KESEJAHTERAAN PENDUDUK HINDIA BELANDA PADA AWAL ABAD XX - Fathoni, Rifai Shodiq (History Department, Faculty of Humanities, University of Jember, 2024)
This study delves into the role played by the Mindere Welvaart Commission in addressing welfare concerns within the Dutch East Indies. Employing the historical method, including heuristics, source criticism, interpretation, and historiography, the study examines the commission's formation and its impact. Findings indicate that the colonial government established the Mindere Welvaart Commission in response to pressure to address the welfare of the indigenous population. While the commission effectively investigated the economic and social issues facing the population, it faced controversy and criticism. Some contemporary figures argued that the commission was formed to delay immediate improvements, while others questioned the accuracy of the presented data. Keywords: Mindere Welvaart; Policy; Ethical Politics; Modernization